The Biodiversity Heritage Library: Empowering Discovery through Free Access to Biodiversity Knowledge - Kalfatovic, Martin; Costantino, Grace (KULA)

(untitled) (University of Victoria Libraries, 2018)
The advancement of knowledge about life on the planet—its origins, preservation, and loss of species and environments—is dependent on access and reference to library collections. The Biodiversity Heritage Library (BHL) is a global digital library that serves the biodiversity research community, as well as a widening circle of those interested in learning more about life. Through an international consortium of natural history and botanical libraries and in close collaboration with researchers, bioinformaticians, publishers, and information technology professionals, BHL has democratized access to biodiversity information and revolutionized research worldwide, allowing everyone, everywhere to study and explore life on Earth.